2015
DOI: 10.1016/j.jaac.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Predictors Associated With Improved Cognitive-Behavioral Therapy Outcome in Pediatric Obsessive-Compulsive Disorder

Abstract: In the multivariate analysis, only age predicted better treatment outcome. Using univariate analysis, a variety of predictors of poorer treatment outcome after CBT was identified. The high impact of comorbid symptoms on outcome in pediatric OCD suggests that treatment should address comorbidity issues. The lack of a family predictor may be related to high family involvement in this study. Future research strategies should focus on optimizing intervention in the presence of these characteristics to achieve grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
1
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 43 publications
2
46
1
7
Order By: Relevance
“…Interestingly, family accommodation does not seem to be associated with the clinical outcome when CBT follows a more intensive family approach [29]. Moreover, tic disorders do not seem to be a predictor of poor outcome either [27,29,30].…”
Section: Cbtmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, family accommodation does not seem to be associated with the clinical outcome when CBT follows a more intensive family approach [29]. Moreover, tic disorders do not seem to be a predictor of poor outcome either [27,29,30].…”
Section: Cbtmentioning
confidence: 92%
“…In addition, up to 30 % show little or no improvement [9,20]. Factors have been found that can predict a poor outcome of CBT, such as higher initial OCD severity [27][28][29], more internalizing and externalizing symptoms/disorders [28][29][30], and family dysfunction or high family accommodation [27,28,31]. Interestingly, family accommodation does not seem to be associated with the clinical outcome when CBT follows a more intensive family approach [29].…”
Section: Cbtmentioning
confidence: 99%
“…In 2 dieser Studien war die Behandlung primär kognitiv ausgerichtet [Bolton et al, 2011;Williams et al, 2010] und ebenso wirksam wie die behavioralen Behandlungen. Die kürzlich veröffentlichte multizentrische skandinavische Nordic Long-term OCD Treatment Study (NordLOTS) belegte die gute Wirksamkeit von CBT auch außerhalb spezialisierter universitärer Einrichtungen [Torp et al, 2015]. Wie Tabelle 1 zu entnehmen ist, bewegen sich die Remissionsraten üblicherweise zwischen 40 und 60%.…”
Section: Empirische Evidenz Zur Behandlungunclassified
“…In der ersten großen Wirksamkeitsstudie [POTS, 2004] [Garcia et al, 2010]. In der NordLOTS zeigte sich nur das Alter als signifikanter Prädiktor: Präpubertäre Kinder sprachen besser auf die Behandlung an als älte-re [Torp et al, 2015]. Rudy et al [2014] untersuchten 3 potenzielle Prädiktorkategorien: demografische Daten (Alter, Geschlecht, Ethnie), Charakteristika der Zwangsstörung (Symptomschwere, Beeinträchtigung, familiäre Akkomodation) und Komorbiditäten.…”
Section: Empirische Evidenz Zur Behandlungunclassified
“…al, 2013). Additional and recent research reported that low-income level is not a significant predictor of outcome in CBT for anxiety (Torp et al, 2015;Walter et al, 2013). Sullivan et al (2013) utilized a CBT intervention for anxiety and noted that clinical improvement between lower income and higher income individuals was similar.…”
mentioning
confidence: 95%